Managing the return to sport of the elite footballer following semimembranosus reconstruction. Issue 1 (24th October 2020) - Taberner, Matt; Haddad, Fares S; Dunn, Andy; Newall, Adam; Parker, Lloyd; Betancur, Esteban; Cohen, Daniel D
Abstract : Hamstring strains are the most common injury in elite football and typically occur during high-speed running. Despite its important contribution to power production in the late swing phase, injury to the semimembranosus (SM) is less common than to the biceps femoris, but may involve the free tendon and depending on the degree of retraction, warrant surgical repair. Few case reports detail clinical reasoning, supported by objective data during rehabilitation in elite footballers, and none have described the return to sport (RTS) process following this type of hamstring injury. In this article, we outline the management and RTS of an English Premier League (EPL) footballer who suffered a high-grade SM proximal tendon tear during training. Due to the degree of retraction of the free tendon, the player underwent surgical reconstruction at the recommendation of an orthopaedic surgeon. Early physiotherapy care, nutritional support, on- and off-pitch injury-specific reconditioning and global athletic development are outlined, alongside strength and power diagnostic and global positioning systems data, assessment of pain, player feedback and MRI informed clinical reasoning and shared decision-making during the RTS process. 18 weeks post-surgery the player returned to team training, transferring to a new club 3 weeks later. 2.5 years post RTS, the player remains free of re-injury playing regularly in the EPL.